Analysing Structural Behaviour under Dynamic Loading with Soil-Structure Interaction (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Several studies have shown that the Soil Structure Interaction plays a major role in the extent of damage caused by the recent earthquakes. It has been discovered that the performance of the structure is greatly impacted by the interaction between the soil and the structure. This research presents the impact of soil-structure interaction on the natural period, vibration mode, damping, and dynamic response of the structure